Asuhan Keperawatan Keluarga Tn. As dengan Gangguan Sistem Muskuloskeletal: (Rheumatoid Arthtritis pada Ny. W Desa Purwodadi, RT 02/RW 03, Kecamatan Tonjong, Kab. Brebes) - Resti Faradila; Esti Nur Janah; Siti Fatimah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Non-Communicable Diseases (NCDs) remain the leading cause of global morbidity and mortality, and one of the chronic conditions included in this group is rheumatoid arthritis (RA). RA is an autoimmune disease that affects the synovial joints, resulting in persistent inflammation, chronic pain, stiffness, and eventual deformities if left untreated. In Indonesia, the burden of RA continues to grow; the prevalence reaches 11.9% based on clinical diagnosis and rises to 24.7% when measured using symptom-based diagnosis. This case study aimed to describe family nursing care for a client with RA through a structured nursing process approach to improve quality of life and family involvement. The study took place in Purwodadi Village, Tonjong Subdistrict, Brebes Regency, focusing on the family of Mr. AS with Mrs. W as the client diagnosed with RA. Data collection involved comprehensive interviews, direct observation, physical examination, and documentation review. Assessment findings included chronic pain with an intensity score of 4, limited mobility, and inadequate family knowledge regarding RA management. Nursing interventions implemented were family education on RA, simple rheumatic exercises tailored to the client’s ability, and the application of warm ginger compresses as a non-pharmacological pain relief method. Post-intervention evaluation showed pain reduction to a score of 2, improved independence in performing light daily activities, and enhanced family understanding and support. In conclusion, family-centered nursing care combined with non-pharmacological interventions can effectively reduce pain, improve mobility, and strengthen the family’s role in supporting RA management.